'It really suits the objectives of the master's': how a student Facebook group chat contributes to situated learning in an interpreter training programme. Issue 3 (3rd July 2021) - Valtchuk, Oleksandra; Class, Barbara
ABSTRACT: In the context of an ever-increasing use of social networks, researchers have studied their use in higher education and the development of communities of practice in formal and informal virtual learning environments. However, no research so far has linked non-institutional group chats and (situated) learning as part of interpreter training. This qualitative study therefore aims to explore how a Facebook group chat amongst students of the University of Geneva's master's programme in Conference Interpreting contributed to learning. The content of the group chat among five students was analysed and complemented by semi-structured interviews. Findings indicate that the group chat is used for study-related content and social conversations and that a (sub-)community of practice has developed among the five students. Findings also show that they think the group chat contributed to their success in the master's programme, both through the close and friendly relationships fostered and academically, although to different extents. Looking at these results against the backdrop of the existing literature could give pointers to students and trainers on how such social networking tools can be used in a beneficial way.